Knowledge Structure and Trends of Vitiligo From 2002 to 2023: A Bibliometric Analysis - Yaqing Wen; Li Lei; Ling Jiang; Chuhan Fu; Shu Zhou; Keyi Zhang; Jiangfeng Huang; Jing Chen; Qinghai Zeng (Mattioli1885, 2024)
Introduction: Vitiligo is a common acquired depigmenting dermatosis resulting from a loss of epidermal melanocytes. The academic attention to vitiligo has gradually increased over the past two decades. Objective: We aimed to explore the current research structure and trends of vitiligo. Methods: Publications about vitiligo from the Web of Science Core Collection (WoSCC) database were searched. VOSviewer, CiteSpace, GraphPad Prism 8, ArcGIS, and Charticulator were implemented for data description and visual analysis. Results: A total of 3,037 publications authored by 10,993 individuals from 2,753 institutions across 88 countries/regions were collected. These publications were published in 616 journals and cited a total of 39,433 references. China was the most productive country. Cairo University and Ezzedine Khaled were the most prolific institution and author, respectively. Additionally, the British Journal of Dermatology stood out as the journal with the highest number of publications. According to the analysis of keywords and references, "quality of life," "depression," and "validation" were hotspots in terms of clinical characteristics, while "prevalence", "comorbidity," "association," and "immunotherapy" gained more research interest with respect to epidemiology and genetics. The frontiers of pathogenesis focused on "unfolded protein response," "migration," "biomarkers," and "CXCL10." As far as treatment is concerned, there was increasing attention to "janus kinase inhibitor," "fractional carbon dioxide laser," "platelet-rich plasma," and "5-fluorouracil." Conclusion: The bibliometric analysis elucidates the foundational knowledge structure on research forces and unveiled the hotspots and frontiers, aiding researchers in gaining a deeper comprehension of the future development trends in the field of vitiligo.